DIGITAL MARKETING TRAINING IN AN EFFORT TO INCREASE SME INCOME IN SOTABAR VILLAGE, PASEAN DISTRICT, PAMEKASAN REGENCY: PELATIHAN DIGITAL MARKETING DALAM UPAYA PENINGKATAN PENDAPATAN UMKM DI DESA SOTABAR KECAMATAN PASEAN KABUPATEN PAMEKASAN - Shofi , Auliya; Aini , Maryatul; Nuurulloh, R. Muhammad Alif; Dian Eswin Wijayanti (Khidmatuna: Jurnal Pengabdian Masyarakat, 2024)
The village of sotabar is one of the villages where the majority of its inhabitants work as fishermen so that some of the village people have a business using processed seafood. In the process of marketing, the village people have not made the most of the Internet media, due to the lack of facilities and information as well as the low human resources in doing digital marketing. As an effort to form UMKM undertakes  sosialization and digital marketing training activities using media such as Google Business WhatsApp Business and Instagram. Public service activities carried out on September 20, 2023 using three methods of implementation: preparation,  sosialization and evaluation. In this activity has made a positive contribution to the improvement of knowledge and skills of UMKM perpetrators regarding digital marketing.